2022
DOI: 10.17645/mac.v10i2.5792
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Social Cohesion: A Double-Edged Sword

Abstract: Social media plays a major role in public communication in many countries. Therefore, it has a large impact on societies and their cohesion. This thematic issue explores the impact social media has on social cohesion on a local or national level. The nine articles in this issue focus on both the potential of social media usage to foster social cohesion and the possible drawbacks of social media which could negatively influence the development and maintenance of social cohesion. In the articles, social cohesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…WhatsApp, as an instant messaging app, invented by Brian Acton and Jan Koum in 2009, has been acknowledged as an important social media platform for information sharing and receiving [38], and it is being utilized among professional groups to disseminate information [38][39][40][41]. Similar to the observations in this study, professional groups have been found to utilize WhatsApp in sharing messages that can advance social cohesion and socialization [42][43][44]. Social cohesion among the group in this study was apparent in the WhatsApp chats, as members addressed themselves using first person pronouns such as we, us, and our group/association.…”
Section: Plos Onesupporting
confidence: 53%
“…WhatsApp, as an instant messaging app, invented by Brian Acton and Jan Koum in 2009, has been acknowledged as an important social media platform for information sharing and receiving [38], and it is being utilized among professional groups to disseminate information [38][39][40][41]. Similar to the observations in this study, professional groups have been found to utilize WhatsApp in sharing messages that can advance social cohesion and socialization [42][43][44]. Social cohesion among the group in this study was apparent in the WhatsApp chats, as members addressed themselves using first person pronouns such as we, us, and our group/association.…”
Section: Plos Onesupporting
confidence: 53%
“…The discourse conducted till now article was focusing on the use of social media in facilitating social/societal change. One needs to understand that with the rise of social media, Internet communication became a doubleedged sword [33,34]. Parting from the perspective of one-way communication (Web 1.0) and becoming interactive (Web 2.0) it enabled two-way communication [8], often based on the reciprocity rule and enabled building a competitive advantage in the context of electronic communication with the use of social media [35].…”
Section: Social Media As a Double-edged Swordmentioning
confidence: 99%
“…Hence, it might be a "time-bomb" for the app since humorous would either harmful or harmless. Moreover, no boundaries on "humorous" content nor commentary insisted onto the cyberbullying (Steer et al, 2020), misinformation (Stieglitz & Ross, 2022), or wasting food. Until the time of writing, there is no significant action from TikTok itself, which resulted in toleration these contents by the public.…”
Section: Trendinessmentioning
confidence: 99%